Reliable Retrieval-Augmented Generation with Evidence Verification and Uncertainty-Aware Response Control - Ricci, Alessandro; Conti, Matteo (Journal of Computer Science and Software Applications, 2025)
Retrieval-augmented generation (RAG) has become an important approach for improving the factual grounding of large language models by incorporating external knowledge during response generation. However, conventional RAG systems still face reliability challenges, including irrelevant retrieval results, incomplete evidence coverage, hallucinated responses, outdated knowledge, and insufficient transparency in source attribution. This paper investigates reliable RAG from the perspective of evidence quality, response faithfulness, and uncertainty-aware generation control. We propose a reliability-oriented RAG framework that integrates multi-stage document retrieval, semantic evidence filtering, source consistency verification, and confidence-based response regulation. The framework first retrieves candidate knowledge from external corpora, then evaluates the relevance and consistency of retrieved evidence before generation. During response construction, the model is guided to prioritize verified evidence and reduce unsupported claims. When the retrieved context is insufficient or conflicting, the system produces uncertainty-aware responses rather than generating overconfident conclusions. Experimental analysis demonstrates that the proposed framework improves answer faithfulness, reduces hallucination rates, and enhances source traceability compared with standard RAG pipelines. The results suggest that reliable RAG requires not only stronger retrieval models, but also systematic evidence verification and generation-time uncertainty control. This study provides a practical direction for building trustworthy, transparent, and enterprise-ready knowledge-intensive LLM applications.